2011
DOI: 10.1111/j.1468-1331.2011.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor features and response to oral levodopa in patients with Parkinson’s disease under continuous dopaminergic infusion or deep brain stimulation

Abstract: STN DBS provided adequate trade-off between motor improvement and dyskinesia control, although dyskinesias could be elicited by adding oral levodopa. Jejunal levodopa infusion produced adequate motor improvement with slow time to 'on' and moderate dyskinesias. Apomorphine infusion produced insufficient motor control and negligible dyskinesias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
(36 reference statements)
3
24
0
7
Order By: Relevance
“…We found that LCIG improves motor fluctuations in spite of the target and results of DBS, but that best outcome is observed in patients who had previously undergone bilateral STN DBS, as confirmed by the only two studies describing the combination use of LCIG and DBS . This finding is also in keeping with a previous study showing that patients on STN DBS are less prone to develop dyskinesias when challenged with high doses of l ‐dopa …”
supporting
confidence: 90%
“…We found that LCIG improves motor fluctuations in spite of the target and results of DBS, but that best outcome is observed in patients who had previously undergone bilateral STN DBS, as confirmed by the only two studies describing the combination use of LCIG and DBS . This finding is also in keeping with a previous study showing that patients on STN DBS are less prone to develop dyskinesias when challenged with high doses of l ‐dopa …”
supporting
confidence: 90%
“…This delay to best motor "On" could arise from the absence of an initial highflow-rate morning dose of jejunal levodopa as was used in the current work, resulting in a longer time required to reach therapeutic levodopa plasma levels (29). This possibility is supported by the fact that the time to best motor "On" was improved when a morning oral dose of levodopa was added in the study of Elia et al (39). Our study is limited in that the effects of LCIG on motor symptoms were not assessed.…”
Section: Discussionsupporting
confidence: 69%
“…A study comparing STN DBS and LCIG reported an overall similar short‐term effect on motor fluctuations, although STN DBS may have been more effective against LID and associated with fewer adverse events . A pharmacological study comparing the acute and chronic effects of L‐dopa in a relatively small group of patients receiving either STN DBS, LCIG, or CSAI concluded that DBS was the best strategy for LID reduction …”
Section: Managementmentioning
confidence: 99%